1985
DOI: 10.1104/pp.79.1.95
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Serine:Glyoxylate Aminotransferase from Cucumber Cotyledons

Abstract: Serine:glyoxylate aminotransferase, a marker enzyme for leaf peroxisomes, has been purified to homogeneity from cucumber cotyledons (Cucamis sativus cv Improved Long Green). The isolation procedure involved precipitation with polyethyleneimine, a two-step ammonium sulfate fractionation (35 to 45%), gel filtration on Ultrogel AcA 34, and ion exchange chromatography on diethylaminoethyl-cellulose, first in the presence of pyridoxal-5-phosphate, and then in its absence. The enzyme was purified approximately 690-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
25
0

Year Published

1987
1987
2003
2003

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 17 publications
2
25
0
Order By: Relevance
“…No activity was found when serine or aspartate were used as amino donors or when glyoxylate was used as a keto donor. Therefore, unlike several other aminotransferases that have been purified (10,12), this isoform is very specific in catalyzing the AlaAT reaction. A second distinctive feature of this enzyme is that PLP does not have any effect on either enzyme activity or column binding.…”
Section: Effect Of Plp On Alaat Activitymentioning
confidence: 99%
See 4 more Smart Citations
“…No activity was found when serine or aspartate were used as amino donors or when glyoxylate was used as a keto donor. Therefore, unlike several other aminotransferases that have been purified (10,12), this isoform is very specific in catalyzing the AlaAT reaction. A second distinctive feature of this enzyme is that PLP does not have any effect on either enzyme activity or column binding.…”
Section: Effect Of Plp On Alaat Activitymentioning
confidence: 99%
“…A number of different researchers have found that PLP affects aminotransferase activity or binding properties to chromatography columns (10,12). We incubated each pooled fraction containing AlaAT activity with 10 mm PLP; however, the presence of PLP had no effect on enzyme activity at any stage of purification.…”
Section: Effect Of Plp On Alaat Activitymentioning
confidence: 99%
See 3 more Smart Citations